Accuracy and quality of animal health information on Social Media: A case study on TikTok - Varmazyar, Reza; NikAhd, Hamed; GonzÃ¡lez-Valiente, Carlos Luis; Pinto, Adilson Luiz (Bibliotecas. Anales de investigación, 2023)
Objective: The purpose of this study is to investigate the 150 top-listed videos on TikTok focused on dogs’ health in order to systematically characterize their types and scientific accuracy. Design/methodology/approach: TikTok was searched for videos about dog health by using the terms “Doghealth”, “Dogdiet”, and “Dogadvice”. Initially, the top 50 videos were considered, and after eliminating the irrelevant videos, the 86 remaining videos were evaluated by the authors on detailed information, then categorized, and lastly, an experienced veterinarian watched each video to assess and rate its accuracy. Results and discussion: The findings indicate that approximately half of the selected videos focused on scientifically confirmed methods for treating pet dogs, while the other half tended to offer more practical approaches. Among the videos created by veterinarians, around two-thirds (67 videos) were grounded in verified scientific methods. However, non-veterinarian videos displayed less scientific reliability, with only 38 percent (20 videos) adhering to verified scientific methods, and a greater emphasis on experimental approaches. Conclusion: The results suggest that TikTok posts about dogs’ health are useful, but not entirely reliable and trustworthy sources of health information. Many posts are beneficial, but not entirely reliable and trustworthy. Originality/value: This paper provides an analysis of the accuracy and quality of 150 top-listed videos on TikTok about dogs’ health.